2022
DOI: 10.1037/trm0000306
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between race-based traumatic stress and the Trauma Symptom Checklist: Does racial trauma differ in symptom presentation?

Abstract: This study examined the relationship between race-based traumatic stress symptoms and traditional trauma symptoms in Black Americans. Although research has shown that experiences of racial discrimination can result in stress and trauma reactions, less is known about how these symptoms present and their relationship with traditional trauma presentation. Participants were 230 community-based Black American adults (58.7% male). Criterion-related profile analysis was used to examine the level and arrangement of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Further, Roberson and Carter 16 explored the link between race-based traumatic stress symptoms and traditional trauma symptoms in Black Americans. Using criterion-related profile analysis, Roberson and Carter were able to analyze the level and arrangement of race-based traumatic stress symptoms that predict trauma reactions in participants who report differing levels of race stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Roberson and Carter 16 explored the link between race-based traumatic stress symptoms and traditional trauma symptoms in Black Americans. Using criterion-related profile analysis, Roberson and Carter were able to analyze the level and arrangement of race-based traumatic stress symptoms that predict trauma reactions in participants who report differing levels of race stress.…”
Section: Introductionmentioning
confidence: 99%
“…Also noteworthy is the fact that hypervigilance was not linked to trauma reactions in people with racial stress. Roberson and Carter 16 concluded that distinct symptom presentations should be considered when measuring trauma caused by racial encounters.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, community members witnessing racial disparities in police shootings can experience vicarious trauma. Race‐based traumatic stress and racial trauma are associated with traditional posttraumatic symptomology (Roberson & Carter, 2021). Exponential negative mental health impacts have been found in black communities for additional police killings of unarmed Black Americans (Bor et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within the development of this measure and conceptualization of racial trauma (Carter & Helms, 2002), these researchers argued that distinct types or classes of racism are likely needed rather than a broad social definition of racism that could entail a wide range of racism experiences over time. In line with this premise, Roberson and Carter (2021) recently completed a study where they utilized the RBTSSS scale to examine the link between differing levels of racism-related stress and the Trauma Symptom Checklist. These researchers created "racial stress-level groups" where the "racial trauma group" was considered to be the label for participants who scored in the highest level on the RBTSSS scale.…”
Section: Rdoc Measurement and Methodological Considerationsmentioning
confidence: 99%
“…Although empirical research continues to grow demonstrating a relationship between racial trauma and PTSD (Roberson & Carter, 2021;Williams, Metzger, Leins, & DeLapp, 2018), researchers have also highlighted the conceptual similarities as well as differences between racial trauma and other traumatic experiences related to PTSD. Racism is considered to be traumatic because like other traumatic experiences outlined in the DSM (i.e., sexual assault, rape, and interpersonal violence) racism is uncontrollable, unpredictable and motivated by the impulse for power (Bryant- Davis & Ocampo, 2005).…”
Section: Definitions and The Biological Embedding Of Racial Traumamentioning
confidence: 99%